The Implementation of Portal Union Catalog Server Sulsellib Based On Senayan Library Management Systems (SLiMS) - Akbar, A. Khaidir; Azwar, Muhammad (STAIN Ponorogo, 2018)
The research attempts to explain Portal Union Catalog Server (UCS) based on Senayan Library Management Systems (SLiMS) in South Sulawesi, Indonesia. Portal UCS becomes the media of technological information in developing cooperation among libraries in searching of the collection in South Sulawesi, Indonesia. This research principally aims to know the implementation of that portal, the obstacles it deals with, and the hope of SLiMS Community on Portal UCS Sulsellib. This research is basically included as a descriptive research using a qualitative approach. As regards to informants as the data sources of research, they are mainly some superintendents and users of Portal UCS Sulsellib. Some research shows that the implementation of Portal UCS Sulsellib can be very helpful for library users in accessing information of collection in various libraries in South Sulawesi because it is only through one door of the portal web of UCS Sulsellib. SLiMS community uses the technic of Waterfall model adapted from System Development Life Cycle (SDLC). The stages of applying this portal are based on waterfall model that is planning, analysis, display design, promotion, implementation, and maintenance. The hope is that this research can extensively upgrade the performance of Portal UCS Sulsellib so that it can be very helpful to explore a collection of information to be more effective and efficient. Besides, it will be used as references to renew the union catalog system.